2020
DOI: 10.3390/info11090436
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Detection Directly from Compressed ECG with the Prior of Measurement Matrix

Abstract: In the wearable health monitoring based on compressed sensing, atrial fibrillation detection directly from the compressed ECG can effectively reduce the time cost of data processing rather than classification after reconstruction. However, the existing methods for atrial fibrillation detection from compressed ECG did not fully benefit from the existing prior information, resulting in unsatisfactory classification performance, especially in some applications that require high compression ratio (CR). In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The slight increase in the performance at the 75% CR was previously studied, and it was found that the filtering effects of the DBBD matrix aided in highlighting the features of AF (Abdelazez et al, 2021). Poian et al (2017), Cheng et al (2020), and Zhang et al ( 2020) developed an equivalent of Stage 2. At 50% and 75% CR, the proposed Stage 2 precision and accuracy were better than the literature (Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The slight increase in the performance at the 75% CR was previously studied, and it was found that the filtering effects of the DBBD matrix aided in highlighting the features of AF (Abdelazez et al, 2021). Poian et al (2017), Cheng et al (2020), and Zhang et al ( 2020) developed an equivalent of Stage 2. At 50% and 75% CR, the proposed Stage 2 precision and accuracy were better than the literature (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Poian et al (2017) utilized the matched filtering technique to detect AF in compressively sensed ECG by locating the heartbeats, extracting RRI features, and using a support vector machine to differentiate ECG with AF from normal ECG. Cheng et al (2020), Zhang et al (2020) proposed using deep learning to detect AF in compressively sensed ECG.…”
Section: Atrial Fibrillation Detectionmentioning
confidence: 99%
“…Other techniques to accelerate arrhythmia detection include real-time data compression, signal processing, and data transmission [ 67 , 68 , 69 ]. Alternatively, ECG data may be compressed to enable real-time AF classification [ 70 , 71 ].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The first is biological signal processing to detect heart disease, and the second is data mining related to variables that trigger heart disease. Research mainly involves electrocardiogram signals processing for the detection of heart disease (Cheng et al, 2020;Hadiyoso & Rizal, 2017;Pestana et al, 2020) or processing heart sounds (Rizal & Suratman, 2020;Zeinali & Niaki, 2022). Heart imaging techniques through echocardiography are also an alternative for the detection of heart disease (Liastuti et al, 2022;Mabrouk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%